Evaluating the potential of Vacuolar ATPase inhibitors as anticancer agents and multigram synthesis of the potent salicylihalamide analog saliphenylhalamide - Lebreton, Sylvain (2008)
The natural product salicylihalamide is a potent inhibitor of the Vacuolar ATPase (V-ATPase), a potential target for antitumor chemotherapy. We generated salicylihalamide-resistant tumor cell lines typified by an overexpansion of lysosomal organelles. We also found that many tumor cell lines upregulate tissue-specific plasmalemmal V-ATPases, and hypothesize that tumors that derive their energy from glycolysis rely on these isoforms to maintain a neutral cytosolic pH. To further validate the potential of V-ATPase inhibitors as leads for cancer chemotherapy, we developed a multigram synthesis of the potent salicylihalamide analog saliphenylhalamide.